2000
DOI: 10.1177/088840640002300206
|View full text |Cite
|
Sign up to set email alerts
|

IDEA '97 and Educator Standards: Special Educators' Perceptions of Their Skil[Is and Those of General Educators

Abstract: The authors provide results of a study analyzing special educator's beliefs regarding special and general educators' skills in implementing legal mandates described in Public Law 105-17, the individuals with Disabilities Education Act (IDEA '97). The authors compare how preservice and practicing special educators approach legal mandates, and what special educators perceive to be the influence of their preservice preparation andlor continuing professional development opportunities on satisfying legal requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Many participants advocated separate settings, separate testing, and separate curricula-a common response to student failure in general education classes on general education exams. This finding is supported by past research that documented special education teachers' skepticism that general education teachers understand special education and are able to make accommodations in their classrooms for students with disabilities (O'Shea, Stoddard, & O'Shea, 2000). Such beliefs may contribute to alienation of new teachers from their general education colleagues and to further entrenchment of the separate-systems approach to general education and special education.…”
Section: (Belden Russonelo Andstewart 2003 P 2)supporting
confidence: 70%
“…Many participants advocated separate settings, separate testing, and separate curricula-a common response to student failure in general education classes on general education exams. This finding is supported by past research that documented special education teachers' skepticism that general education teachers understand special education and are able to make accommodations in their classrooms for students with disabilities (O'Shea, Stoddard, & O'Shea, 2000). Such beliefs may contribute to alienation of new teachers from their general education colleagues and to further entrenchment of the separate-systems approach to general education and special education.…”
Section: (Belden Russonelo Andstewart 2003 P 2)supporting
confidence: 70%
“…Findings from a survey conducted in the United States by O'Shea et al (2000) seemed to provide a somewhat different view of teachers' knowledge about assessment. Their study showed that experienced special education teachers were more knowledgeable about formal types of assessments, such as standardized tests, whereas novice special education teachers were more knowledgeable about informal, diagnostic uses of assessment.…”
Section: Teachers' Assessment Knowledgementioning
confidence: 83%
“…Therefore, our most emphatic recommendation is that those with an interest in assessment-novice teachers, teacher educators, indeed measurement experts themselves-deploy various formal and informal methods for surfacing, paying attention to, and then grounding their own work in the insights of experienced teachers (cf. O'Shea et al, 2000).…”
Section: Interpretation and Recommendationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Current research into teacher attitudes has shown that both general and special education teachers are in the main, supportive of the principle of inclusion (Minke, Bear, Deemer, & Griffin, 1999;O'Shea, Stoddard, & O'Shea, 2000;Semmel, Abernathy, Butera, & Lesar, 1991), although some teachers have also been found to be of the opinion that inclusion, though desirable, may not be practicable in reality (Schumm & Vaughn, 1991). Some differences, however, have been reported between general and special education teachers.…”
mentioning
confidence: 97%